1991
DOI: 10.1128/jb.173.16.5173-5180.1991
|View full text |Cite
|
Sign up to set email alerts
|

Electrophoretic separation of the three Rhizobium meliloti replicons

Abstract: The megaplasmids and the chromosome from the bacterium Rhizobium meliloti 1021 were separated in preparative quantities by using transverse alternating-field gel electrophoresis. The genetic content of each electrophoretically separated band was determined by Southern hybridization with replicon-specific probes and by comparison with Agrobacterium tumefaciens transconjugants harboring either pSym-a or pSym-b megaplasmids. Pulsed-field gel electrophoresis analyses of PacI (5'-TTAATTAA-3') and SwaI (5'-ATTTAAAT-… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

6
65
0
1

Year Published

1992
1992
2000
2000

Publication Types

Select...
9
1

Relationship

1
9

Authors

Journals

citations
Cited by 85 publications
(72 citation statements)
references
References 39 publications
(40 reference statements)
6
65
0
1
Order By: Relevance
“…A number of restriction maps of bacterial genomes have been constructed by using endonucleases that cleave infrequently (22) and then separating the resulting fragments by pulsed-field gel electrophoresis (PFGE) (2,5,7,8,10,17,19,20,(25)(26)(27)(28)(29)(30)(31)(32)(33)(34)(36)(37)(38)(39). The physical order of these fragments has usually been determined by using Southern blotting with genetically mapped probes such as cloned genes (34) or transposons (38) or by hybridization of fragments from one restriction digest to fragments from a different digest (1,4).…”
mentioning
confidence: 99%
“…A number of restriction maps of bacterial genomes have been constructed by using endonucleases that cleave infrequently (22) and then separating the resulting fragments by pulsed-field gel electrophoresis (PFGE) (2,5,7,8,10,17,19,20,(25)(26)(27)(28)(29)(30)(31)(32)(33)(34)(36)(37)(38)(39). The physical order of these fragments has usually been determined by using Southern blotting with genetically mapped probes such as cloned genes (34) or transposons (38) or by hybridization of fragments from one restriction digest to fragments from a different digest (1,4).…”
mentioning
confidence: 99%
“…The rice nucleus is 3-5 jum in diameter, relatively smaller than that of other plants, which is likely due to the smaller genome size (6-9 x 108 bp) (24). It is also known that the rice nucleus cannot be stained with acetocarmine solution, as in the case of Arabidopsis thaliana Four ml of crude homogenates from dry rice embryos were layered on 12ml of 15-50% continuous Percoll gradient and centrifuged at 6,800rpm for 30min in a Beckman SW-27.1 rotor.…”
Section: Methodsmentioning
confidence: 99%
“…(Lin et al, 1993), Borrelia (Ferdows & Barbour, 1989), and Agrobacterium (Allardet-Servent et al, 1993). Also some bacterial species of the genera Pseudomonas (Frantz & Chakrabarty, 1986), Rhizobium (Sobral et al, 1991), and Alcaligenes (Rodley et al, 1995) harbour very large accessory genetic elements (megaplasmids) which appear to encode ' housekeeping ' functions (Finan et al, 1986;Pardo et al, 1994) ; however their 'essentiality' has not been demonstrated. These findings raise the question : what, if anything, defines a bacterial chromosome?…”
Section: Multiple Chromosomes and Gene Duplication In Prokaryotesmentioning
confidence: 99%